Composite membrane of hollow nanofiber with in-situ grown metal organic framework inside and preparation method thereof
Patent Information
- Application Number
- CN202410481813.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-22
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-04-22
AI Technical Summary
但在中空纳米纤维内部原位生长MOF的制备方法还没有报道过
1. 合成MOF的金属盐和有机配体分别添加到内芯纺丝液和外壳纺丝液中,在纳米纤维内部限域空间生长MOF,降低了传统溶液中生长MOF原料的用量。此外,核壳纳米纤维内芯溶解形成中空结构与内部MOF的原位生长同时进行,减少了操作步骤和有机溶剂的使用,符合绿色化学和清洁生产的要求。
Smart Images

Figure CN118079669B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of nanofunctional composite materials and polymer membrane materials, specifically relating to a composite membrane with a metal-organic framework grown in situ inside hollow nanofibers and its preparation method. Background Technology
[0002] Metal-organic frameworks (MOFs) are long-range ordered porous nanomaterials formed by the self-assembly of metal ions and organic ligands. They possess advantages such as very high specific surface area and tunable pore structure, and have wide applications in separation, adsorption, catalytic detection, and other fields. However, since synthesized MOFs are generally nanoparticles, exhibiting a macroscopic powder morphology, they are difficult to recycle and reuse, limiting practical industrial applications. Therefore, combining MOFs with flexible polymer membrane materials, especially immobilizing MOF nanoparticles on nanofiber membranes prepared by electrospinning, to prepare MOF functionalized composite membrane materials has great development potential.
[0003] Currently, there are four main methods for immobilizing MOFs and nanofibers: (1) direct blending method, which involves dispersing pre-synthesized MOFs in a polymer solution and directly electrospinning to obtain nanofibers mixed with MOFs. However, this results in the polymer covering most of the MOFs and reducing their adsorption performance. Therefore, it is necessary to add a pore-forming agent to create a porous structure, as shown in patents CN116832786A and CN117210960A; (2) spray coating composite method, which involves electrospinning pre-synthesized MOF nanoparticles while preparing nanofibers, so that the MOFs adhere to the surface of the nanofibers and between the fibers, as shown in patent CN113921901A. However, the MOFs in the composite material obtained by this method are not firmly bonded and are easily detached and lost; (3) surface growth. Method (3) involves pre-spinning nanofiber membranes, modifying the membrane surface to introduce active sites suitable for MOF growth (e.g., patent CN116732784A hydrolyzes nanofibers to give them amino and carboxyl groups; patent CN116979111A modifies the surface of nanofibers to generate polydopamine, giving them amino and sulfonic acid groups). The modified nanofiber membrane is then immersed in a solution containing metal ions and organic ligands to grow a layer of MOF crystals on the nanofiber surface. (4) Seed growth method involves mixing metal salts and polymer solutions for spinning, then immersing the nanofiber membrane in a solution containing organic ligands to use the metal ions on the nanofiber surface as induced seeds to grow a layer of MOF crystals, such as patents CN111013271A and CN117026631A. Methods (3) and (4) are characterized by MOF growth on the outer surface of nanofibers, which leads to problems of MOF particle deposition, aggregation, and peeling, which can easily cause secondary pollution and reduce the long-term stability of the composite membrane material.
[0004] Based on conventional electrospinning, two spinning solutions are passed separately into coaxial spinning needles with nested inner and outer structures to obtain core-shell nanofibers. The inner core material is then dissolved and removed to obtain hollow nanofiber membranes with tubular structures. The internal cavities can embed and immobilize bioactive molecules, as illustrated in patents CN102733000A and CN113249811A. However, methods for preparing MOFs by in-situ growth inside hollow nanofibers have not yet been reported. Summary of the Invention
[0005] To address the aforementioned problems, this invention provides a composite membrane with in-situ growth of metal-organic frameworks (MOFs) inside hollow nanofibers and its preparation method. Electrospinning is performed using a coaxial needle. Organic ligands are added to the outer shell spinning solution, and metal salts are added to the inner core spinning solution. First, a core-shell nanofiber membrane is prepared. Then, the core-shell nanofibers are immersed in a specific solution and heated for a certain period. While the inner core material dissolves to form a hollow structure, metal ions in the inner core diffuse outward and contact the organic ligand seeds exposed on the inner surface of the outer shell polymer, thereby in-situ growing MOF crystals within the tubular cavities inside the hollow nanofibers.
[0006] The present invention adopts the following technical solution: A composite membrane in which a metal-organic framework is grown in situ inside hollow nanofibers is disclosed. The composite membrane is a hollow nanofiber membrane. The organic ligands of the metal-organic framework are dissolved in the spinning solution that forms the outer shell, and the metal salts corresponding to the metal-organic framework are dissolved in the spinning solution that forms the inner core. The two processes of hollow structure formation and in-situ growth of the metal-organic framework are carried out simultaneously, and the generated metal-organic framework is located in the internal cavity of the hollow nanofiber.
[0007] A method for preparing a composite membrane in which a metal-organic framework is grown in situ inside hollow nanofibers includes the following steps: The first step involves dissolving a polymer in an organic solvent, adding an organic ligand, and stirring to obtain a transparent solution, which serves as the outer shell spinning solution for coaxial electrospinning. A metal salt is dissolved in an aqueous solution and then added to glycerol and mixed thoroughly to serve as the inner core spinning solution for coaxial electrospinning. The second step involves adding the inner core spinning solution and the outer shell spinning solution into two syringes, which are then connected to the inner and outer inlets of a coaxial needle via tubing. Two micro-injection pumps are used to control the flow rates of the outer shell spinning solution and the inner core spinning solution, respectively. Voltage is applied to perform electrospinning, and the core-shell nanofiber membrane is collected at the receiving end. The third step involves immersing the core-shell nanofiber membrane in a specific solution and heating it. Then, the nanofiber membrane is removed, cleaned, and dried to obtain a composite membrane material in which a metal-organic framework is grown in situ inside hollow nanofibers.
[0008] Further, the polymer mentioned in the first step includes any one of polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polystyrene (PS), and polyvinylidene fluoride-hexafluoropropylene (P(VDF-HFP)); the organic solvent includes one or more combinations of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), acetone, N-methylpyrrolidone (NMP), tetrahydrofuran, dimethyl sulfoxide, and dichloromethane.
[0009] Furthermore, the organic ligands mentioned in the first step include one or more combinations of imidazoles, carboxylic acids, porphyrins, pyridines, phenols, terephthalic acids, and trimesic acids.
[0010] Furthermore, in the first step, the mass fraction of the polymer in the outer shell spinning solution is 8%-30%, and the organic ligand accounts for 2%-25% of the mass fraction of the polymer.
[0011] Further, the metal ions in the metal salt mentioned in the first step include one or more combinations of zinc, cobalt, copper, iron, zirconium, cerium, manganese, and nickel, and the molar ratio of the metal salt to the organic ligand is 1:1 to 1:100; the aqueous solution includes pure water or a 0.05-0.5 mol / L solution prepared with acetate, phosphate, or hydrochloric acid and sodium hydroxide at pH=3-9; the volume ratio of the aqueous solution to glycerol in the inner core spinning solution is 1:9.
[0012] Furthermore, in the second step, the flow rate of the outer shell spinning solution is 1.2~2 mL / h, and the flow rate of the inner core spinning solution is 0.2~0.6 mL / h; the voltage is 10~25 kV.
[0013] Furthermore, the specific solution mentioned in the third step includes any one of pure water, 0.1-1 mol / L sodium hydroxide aqueous solution, anhydrous methanol, anhydrous ethanol, and acetone; the heating temperature is 40-120℃, and the heating time is 2-24 hours; the cleaning is three times each with pure water and ethanol; and the drying is vacuum drying at 20-80℃ for 4-12 hours.
[0014] This invention first prepares a core-shell nanofiber membrane with an outer shell containing organic ligands and an inner core containing metal ions by coaxial electrospinning. Then, a hydrothermal / solvothermal reaction is carried out. While the inner core material dissolves to form a hollow structure, MOF crystals grow in situ inside the nanofibers, ultimately obtaining a hollow nanofiber composite membrane with MOFs grown inside. The organic ligands of MOFs are dissolved in the outer shell spinning solution, and the metal salts corresponding to MOFs are dissolved in the inner core spinning solution. The two processes of hollow structure formation and in-situ MOF growth occur simultaneously, and the generated MOF crystals are located in the internal cavity of the hollow nanofibers.
[0015] The beneficial effects of this invention are as follows: 1. The metal salt and organic ligand for synthesizing MOFs are added to the core spinning solution and shell spinning solution, respectively, to grow MOFs in a confined space inside the nanofibers, reducing the amount of raw materials used in traditional solution-based MOF growth. Furthermore, the dissolution of the core-shell nanofiber core to form a hollow structure occurs simultaneously with the in-situ growth of the internal MOF, reducing operational steps and the use of organic solvents, thus meeting the requirements of green chemistry and clean production.
[0016] 2. The metal ions synthesized in MOFs dissolve and diffuse from the core outwards, and come into contact with the organic ligands mixed with the outer shell polymer at the internal interface of the tubular cavity. This restricts the MOFs to preferentially grow in situ inside the nanofibers rather than being deposited on the outer surface and in the solution, thus maintaining the original surface structure and flexibility of the hollow nanofiber outer shell polymer.
[0017] 3. Since MOFs are confined to the interior of hollow nanofibers, the aggregation of MOF nanoparticles is greatly reduced, providing more active sites. It also solves the problem of loss due to MOFs being fixed to the outer surface of nanofibers in existing technologies, thus improving the long-term stability of MOF functionalized composite membranes. Attached Figure Description
[0018] Figure 1 This is a schematic diagram illustrating the preparation of the metal-organic framework composite membrane grown in situ inside the hollow nanofibers of the present invention.
[0019] Figure 2 These are X-ray diffraction patterns of the PVDF core-shell nanofiber membrane prepared in Example 1 and the ZIF-8@PVDF hollow nanofiber composite membrane prepared in Example 2 of this invention.
[0020] Figure 3 This is an EDS surface elemental analysis diagram of the ZIF-8@PVDF hollow nanofiber composite membrane prepared in Example 2 of the present invention.
[0021] Figure 4 This is a scanning electron microscope (SEM) image of the ZIF-8@PVDF hollow nanofiber composite membrane prepared in Example 2 of this invention.
[0022] Figure 5 These are flexible test photos of the ZIF-8@PVDF hollow nanofiber composite membrane prepared in Example 2 of this invention, which are subjected to bending and winding.
[0023] Figure 6 This is a scanning electron microscope (SEM) image of the PCN-222(Fe)@PAN hollow nanofiber composite membrane prepared in Example 3 of this invention. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0025] Example 1 The preparation method of PVDF core-shell nanofiber membrane with an outer shell containing 2-methylimidazole and an inner core containing zinc ions is as follows: 1.2 g of PVDF was dissolved in an organic solvent consisting of 9 mL of DMF and 1 mL of acetone. 0.25 g of 2-methylimidazole was added and stirred until dissolved, yielding a transparent solution used as the outer shell spinning solution. 0.0408 g of Zn(NO3)2•6H2O was dissolved in 0.3 mL of pure water, and then 2.7 mL of glycerol was added and mixed thoroughly to obtain the inner core spinning solution. The molar ratio of zinc nitrate to 2-methylimidazole was 1:40. The two spinning solutions were added to two syringes, which were connected to the inner and outer inlets of a coaxial needle via tubing. The diameter of the outer shell nozzle was 1.138 mm, and the diameter of the inner core nozzle was 0.397 mm. The flow rates of the outer shell and inner core spinning solutions were controlled by a micro-injection pump to be 1.2 mL / h and 0.2 mL / h, respectively. A +14 kV high-voltage electrostatic charge was applied, with a distance of 15 cm between the coaxial needle and the receiver. PVDF core-shell nanofiber membranes were collected after 4 hours of spinning.
[0026] Example 2 The preparation method of ZIF-8@PVDF hollow nanofiber composite membrane is as follows: The PVDF core-shell nanofiber membrane prepared in Example 1 was cut into 4×4 cm samples, placed in a reaction vessel, and then 10 mL of pure water was added. The mixture was heated at 65°C for 4 hours. The nanofiber membrane with ZIF-8 growth was then removed, washed three times each with pure water and ethanol, and then placed in an oven to be vacuum dried at 40°C for 4 hours to obtain the ZIF-8@PVDF hollow nanofiber composite membrane.
[0027] Figure 2X-ray diffraction patterns of the PVDF core-shell nanofiber membrane prepared in Example 1 and the ZIF-8@PVDF hollow nanofiber composite membrane prepared in Example 2 are shown. Characteristic diffraction peaks at 2θ = 7.43°, 10.47°, 12.81°, 14.76°, 16.56°, and 18.08° correspond to the (011), (002), (112), (022), (013), and (222) crystal planes of the ZIF-8 crystal, respectively. A strong carbon diffraction peak at 2θ = 20.5° corresponds to the PVDF polymer. The results indicate that the PVDF core-shell nanofiber membrane prepared in Example 1, although containing 2-methylimidazolium in the outer shell and zinc ions in the core, did not undergo a hydrothermal reaction and did not grow ZIF-8 crystals. However, after a hydrothermal reaction, the ZIF-8@PVDF hollow nanofiber composite membrane prepared in Example 2 successfully grew ZIF-8 crystals inside.
[0028] Figure 3 This is an EDS surface elemental analysis diagram of the ZIF-8@PVDF hollow nanofiber composite membrane prepared in Example 2 of this invention. The outer shell material of the hollow nanofibers is composed of PVDF polymer, containing F and C elements, while ZIF-8 is synthesized from zinc nitrate and 2-methylimidazole, containing Zn and N elements, respectively. The results show that F and C elements are densely distributed on the material surface and constitute the shape of the nanofibers, while the distribution of Zn and N elements is sparse, and the distributions of Zn and N elements do not overlap densely, proving that ZIF-8 crystals are not loaded on the outer surface of the hollow nanofibers, but rather grow in situ inside the hollow nanofibers.
[0029] Figure 4 This is a scanning electron microscope (SEM) image of the ZIF-8@PVDF hollow nanofiber composite membrane prepared in Example 2 of the present invention. No ZIF-8 nanoparticles were observed on the outer surface of the hollow nanofibers, indicating that ZIF-8 is grown in situ in the cavity inside the nanofibers.
[0030] Figure 5 These are flexible test photos of the ZIF-8@PVDF hollow nanofiber composite membrane prepared in Example 2 of the present invention, which shows that the PVDF hollow nanofiber composite membrane with ZIF-8 grown inside still has good flexibility.
[0031] Example 3 The preparation method of PCN-222(Fe)@PAN hollow nanofiber composite membrane is as follows: 6 g of PAN was dissolved in an organic solvent consisting of 38 mL of DMF and 2 mL of dichloromethane. 0.842 g of tetracarboxyphenylporphyrin iron (TCPP-Fe(Ⅱ)) and 0.488 g of benzoic acid were added, and the mixture was stirred to obtain a transparent solution, which served as the outer shell spinning solution. 0.32 g of ZrOCl2•8H2O was dissolved in 2 mL of pure water, and then 18 mL of glycerol was added and mixed thoroughly to obtain the inner core spinning solution. Both spinning solutions were added to two syringes, which were connected to the inner and outer inlets of a coaxial needle via tubing. The flow rates of the outer shell and inner core spinning solutions were controlled by a micro-injection pump to be 2 mL / h and 0.6 mL / h, respectively. A +15 kV high-voltage electrostatic discharge was applied, with the coaxial needle and receiver 15 cm apart. After 8 hours of spinning, the PAN core-shell nanofiber membrane was collected.
[0032] The PAN core-shell nanofiber membrane was cut into 4×4 cm samples, placed in a reaction vessel, and then 10 mL of anhydrous ethanol was added. The mixture was heated at 120℃ for 2 hours. The nanofiber membrane with PCN-222(Fe) growth was then removed, washed three times each with pure water and ethanol, and then placed in an oven to be vacuum dried at 60℃ for 8 hours to obtain the PCN-222(Fe)@PAN hollow nanofiber composite membrane.
[0033] Figure 6 This is a scanning electron microscope (SEM) image of the PCN-222(Fe)@PAN hollow nanofiber composite membrane prepared in Example 3 of the present invention. No PCN-222(Fe) nanoparticles were observed on the outer surface of the hollow nanofibers, indicating that PCN-222(Fe) is loaded in the internal cavity of the nanofibers.
[0034] Example 4 The preparation method of Fe-BTC@PAN hollow nanofiber composite membrane is as follows: 2 g of PAN was dissolved in 20 mL of DMF, and 0.263 g of trimesic acid (BTC) was added and stirred to obtain a transparent solution, which was used as the outer shell spinning solution. 0.508 g of FeCl3•6H2O was dissolved in 1 mL of pure water, and then 9 mL of glycerol was added and mixed thoroughly to obtain the inner core spinning solution. The two spinning solutions were added to two syringes respectively, and connected to the inner and outer inlets of a coaxial needle through tubing. The flow rates of the outer shell spinning solution and the inner core spinning solution were controlled by adjusting the micro-injection pump to 1.5 mL / h and 0.5 mL / h respectively. A +15 kV high voltage electrostatic charge was applied, and the distance between the coaxial needle and the receiver was 15 cm. After spinning for 6 hours, the PAN core-shell nanofiber membrane was collected.
[0035] The PAN core-shell nanofiber membrane was cut into 4×4 cm samples and placed in a reaction vessel. Then, 10 mL of 0.1 mol / L NaOH aqueous solution was added, and the mixture was heated at 60 °C for 4 hours. The Fe-BTC nanofiber membrane was then removed, washed three times each with pure water and ethanol, and placed in an oven to be vacuum dried at 60 °C for 12 hours to obtain the Fe-BTC@PAN hollow nanofiber composite membrane.
[0036] Example 5 The preparation method of the bimetallic organic framework BMZIF@PVDF hollow nanofiber composite membrane is as follows: 1.5 g of PVDF was dissolved in an organic solvent consisting of 9 mL of DMF and 1 mL of acetone. 0.35 g of 2-methylimidazole was added and stirred until dissolved to obtain a transparent solution, which served as the outer shell spinning solution. 0.047 g of cobalt acetate and 0.053 g of zinc acetate were dissolved in 0.3 mL of pure water, and then 2.7 mL of glycerol was added and mixed thoroughly to obtain the inner core spinning solution. The two spinning solutions were added to two syringes, which were connected to the inner and outer inlets of a coaxial needle via tubing. The flow rates of the outer shell and inner core spinning solutions were controlled by a micro-injection pump to be 1.5 mL / h and 0.3 mL / h, respectively. A +13 kV high-voltage electrostatic discharge was applied, with the coaxial needle and receiver at a distance of 15 cm. Spinning was carried out for 4 hours, and the PVDF core-shell nanofiber membrane was collected.
[0037] The PVDF core-shell nanofiber membrane was cut into 4×4 cm samples, placed in a reaction vessel, and then 10 mL of pure water was added. The mixture was heated at 85℃ for 4 hours. The nanofiber membrane with BMZIF growth was then removed, washed three times each with pure water and ethanol, and then placed in an oven to be vacuum dried at 40℃ for 8 hours to obtain the BMZIF@PVDF hollow nanofiber composite membrane.
[0038] Example 6 The preparation method of MIL101(Fe)-NH2@PAN hollow nanofiber composite membrane is as follows: 1 g of PAN was dissolved in 10 mL of DMF, and 0.1 g of 2-aminoterephthalic acid (BDC-NH2) was added and stirred to obtain a transparent solution as the outer shell spinning solution. 0.2 g of FeCl3•6H2O was dissolved in 0.3 mL of a 0.1 mol / L acetate-sodium acetate solution with pH=3, and then 2.7 mL of glycerol was added and mixed thoroughly to obtain the inner core spinning solution. The two spinning solutions were added to two syringes, which were connected to the inner and outer inlets of a coaxial needle via tubing. The flow rates of the outer shell and inner core spinning solutions were controlled by a micro-injection pump to be 1.2 mL / h and 0.3 mL / h, respectively. A +15 kV high-voltage electrostatic discharge was applied, with the coaxial needle and receiver at a distance of 25 cm. After spinning for 10 hours, the PAN core-shell nanofiber membrane was collected.
[0039] The PAN core-shell nanofiber membrane was cut into 4×4 cm samples, placed in a reaction vessel, and then 10 mL of anhydrous ethanol was added. The mixture was heated at 120℃ for 8 hours. The nanofiber membrane with MIL101(Fe)-NH2 grown was then removed, washed three times each with pure water and ethanol, and then placed in an oven to be vacuum dried at 60℃ for 12 hours to obtain the MIL101(Fe)-NH2@PAN hollow nanofiber composite membrane.
[0040] Example 7 The preparation method of UiO-66-NH2@PVDF hollow nanofiber composite membrane is as follows: 1 g of PVDF was dissolved in an organic solvent consisting of 7 mL of DMF and 3 mL of acetone. 0.2 g of 2-aminoterephthalic acid (BDC-NH2) was added, and the solution was stirred until dissolved to obtain a transparent solution, which served as the outer shell spinning solution. 0.1 g of ZrOCl2•8H2O was dissolved in 0.3 mL of pure water, and then 2.7 mL of glycerol was added and mixed thoroughly to obtain the inner core spinning solution. Both spinning solutions were added to two syringes, which were connected to the inner and outer inlets of a coaxial needle via tubing. The flow rates of the outer shell and inner core spinning solutions were controlled by a micro-injection pump to be 2 mL / h and 0.6 mL / h, respectively. A +16 kV high-voltage electrostatic discharge was applied, with the coaxial needle and receiver at a distance of 20 cm. PVDF core-shell nanofiber membranes were collected after 4 hours of spinning.
[0041] The PVDF core-shell nanofiber membrane was cut into 4×4 cm samples, placed in a reaction vessel, and then 10 mL of acetone was added. The mixture was heated at 100℃ for 12 hours. The nanofiber membrane with UiO-66-NH2 growth was then removed, washed three times each with pure water and ethanol, and then placed in an oven to be vacuum dried at 60℃ for 12 hours to obtain the UiO-66-NH2@PVDF hollow nanofiber composite membrane.
[0042] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A composite membrane in which a metal-organic framework is grown in situ inside hollow nanofibers, characterized in that: The composite membrane is a hollow nanofiber membrane. The organic ligands of the metal-organic framework are dissolved in the spinning solution that forms the outer shell, and the metal salts corresponding to the metal-organic framework are dissolved in the spinning solution that forms the inner core. The two processes of hollow structure formation and in-situ growth of metal-organic framework are carried out simultaneously, and the generated metal-organic framework is located in the internal cavity of the hollow nanofiber. The method for preparing the composite membrane includes the following steps: The first step involves dissolving a polymer in an organic solvent, adding an organic ligand, and stirring to obtain a transparent solution, which serves as the outer shell spinning solution for coaxial electrospinning. A metal salt is dissolved in an aqueous solution and then added to glycerol and mixed thoroughly to serve as the inner core spinning solution for coaxial electrospinning. The aqueous solution includes pure water or a solution with pH = 3-9 prepared from acetate, phosphate or hydrochloric acid and sodium hydroxide; The second step involves adding the inner core spinning solution and the outer shell spinning solution into two syringes, which are then connected to the inner and outer inlets of a coaxial needle via tubing. Two micro-injection pumps are used to control the flow rates of the outer shell spinning solution and the inner core spinning solution, respectively. Voltage is applied to perform electrospinning, and the core-shell nanofiber membrane is collected at the receiving end. The third step involves immersing the core-shell nanofiber membrane in a specific solution and heating it, then removing the nanofiber membrane for cleaning and drying to obtain a composite membrane in which a metal-organic framework is grown in situ inside hollow nanofibers. The specific solution includes any one of pure water, 0.1-1 mol / L sodium hydroxide aqueous solution, anhydrous methanol, anhydrous ethanol, and acetone.
2. A method for preparing a composite membrane with an in-situ grown metal-organic framework inside hollow nanofibers as described in claim 1, characterized in that: Includes the following steps: The first step involves dissolving a polymer in an organic solvent, adding an organic ligand, and stirring to obtain a transparent solution, which serves as the outer shell spinning solution for coaxial electrospinning. A metal salt is dissolved in an aqueous solution and then added to glycerol and mixed thoroughly to serve as the inner core spinning solution for coaxial electrospinning. The aqueous solution includes pure water or a solution with pH = 3-9 prepared from acetate, phosphate or hydrochloric acid and sodium hydroxide; The second step involves adding the inner core spinning solution and the outer shell spinning solution into two syringes, which are then connected to the inner and outer inlets of a coaxial needle via tubing. Two micro-injection pumps are used to control the flow rates of the outer shell spinning solution and the inner core spinning solution, respectively. Voltage is applied to perform electrospinning, and the core-shell nanofiber membrane is collected at the receiving end. The third step involves immersing the core-shell nanofiber membrane in a specific solution and heating it, then removing the nanofiber membrane for cleaning and drying to obtain a composite membrane in which a metal-organic framework is grown in situ inside hollow nanofibers. The specific solution includes any one of pure water, 0.1-1 mol / L sodium hydroxide aqueous solution, anhydrous methanol, anhydrous ethanol, and acetone.
3. The method for preparing a composite membrane with an in-situ grown metal-organic framework inside hollow nanofibers according to claim 2, characterized in that: The polymer mentioned in the first step includes any one of polyvinylidene fluoride, polyacrylonitrile, polystyrene, and polyvinylidene fluoride-hexafluoropropylene; the organic solvent includes one or more combinations of N,N-dimethylformamide, N,N-dimethylacetamide, acetone, N-methylpyrrolidone, tetrahydrofuran, dimethyl sulfoxide, and dichloromethane.
4. The method for preparing a composite membrane with an in-situ grown metal-organic framework inside hollow nanofibers according to claim 2, characterized in that: The organic ligands mentioned in the first step include one or more combinations of imidazoles, carboxylic acids, porphyrins, pyridines, phenols, terephthalic acids, and trimesic acids.
5. The method for preparing a composite membrane with an in-situ grown metal-organic framework inside hollow nanofibers according to claim 2, characterized in that: In the first step, the mass fraction of the polymer in the shell spinning solution is 8%-30%, and the organic ligand accounts for 2%-25% of the mass fraction of the polymer.
6. The method for preparing a composite film with an in-situ grown metal-organic framework inside hollow nanofibers according to claim 2, characterized in that: The metal ions in the metal salt mentioned in the first step include one or more combinations of zinc, cobalt, copper, iron, zirconium, cerium, manganese, and nickel, and the molar ratio of the metal salt to the organic ligand is 1:1 to 1:100; the volume ratio of the aqueous solution to glycerol in the inner core spinning solution is 1:
9.
7. The method for preparing a composite membrane with an in-situ grown metal-organic framework inside hollow nanofibers according to claim 2, characterized in that: In the second step, the flow rate of the outer shell spinning solution is 1.2~2 mL / h, and the flow rate of the inner core spinning solution is 0.2~0.6 mL / h; the voltage is 10~25 kV.
8. The method for preparing a composite membrane with an in-situ grown metal-organic framework inside hollow nanofibers according to claim 2, characterized in that: The heating temperature in the third step is 40-120℃, and the heating time is 2-24 hours; the cleaning is to wash three times each with pure water and ethanol; the drying is to vacuum dry at 20-80℃ for 4-12 hours.
Citation Information
Patent Citations
Preparation method for hollow polymer nanofibers
CN102733000A
Nanofiber-loaded metal organic framework air purification material and preparation method thereof
CN111013271A
Preparation method of immobilized bio-enzyme in hollow nanofiber
CN113249811A
Metal organic framework-based composite nanofiber membrane as well as preparation method and application thereof
CN113921901A
Method for preparing MOF (Metal Organic Framework) functionalized nanofiber composite proton exchange membrane
CN116732784A